APLIKASI TEKNOLOGI PEMBELAJARAN DALAM MENGATASI PERMASALAHAN PEMBELAJARAN MATA KULIAH PENCAK SILAT - Nur Rohmah Muktiani (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
Instructional technology is theory and practice of design, development, utilization, management and evaluation of processes and recources for learning. The aims of instructional technology is to ease, to stimulate, to facilitate, and to encourage learning process. The ultimate goal of learning is changing on cognition, skills, and affection which are relatively permanent. In pencak silat course, the need to improve its learning process is critical. This can be enhanced by implementing instructional technology in the learning. Kata kunci : Teknologi pembelajaran, Permasalahan pembelajaran.